Leveraging transmedia content to reach and support underserved children. Issue 2 (2nd April 2016) - Johnson, Pamela; Steven, Devon; Lovitts, Barbara E.; Lowenstein, David; Rodriguez, Jennifer
Abstract: This paper presents public media's national–local model for providing high-quality educational transmedia to America's children as part of the US Department of Education's Ready to Learn (RTL) program. Using connected, multiplatform content as an innovative way to help narrow the academic achievement gap for underserved children, the Corporation for Public Broadcasting (CPB), Public Broadcasting Service (PBS), and local public media stations coordinated efforts to overcome access issues and better reach children from low-income families. This required strong local partnerships and new approaches to implementing content in diverse learning settings. Topics explored in this paper include: (1) RTL's mission to serve all children, (2) narrowing the achievement gap through transmedia, (3) highlights of new PBS KIDS math content funded by RTL, (4) making digital content accessible to low-income families, (5) public media's national-local service model, and (6) community engagement examples from Ohio and Washington.